Pengaruh konten akun tiktok whitelab terhadap minat beli skincare bagi mahasiswa Fakultas Komunikasi dan Informatika Universitas Muhammadiyah Surakarta - Rahayu, Wulan Devita; Santoso, Budi (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2026)
Abstract The rapid growth of social media, particularly video-based platforms like TikTok, has transformed the way consumers, especially younger generations, obtain information and make purchasing decisions. These platforms are utilized by various brands, including Whitelab, to deliver engaging and informative promotional content aimed at shaping perceptions and boosting consumer purchase interest. The objective of this study is to analyze the impact of Whitelab’s TikTok content on purchase interest in skincare products among students in the Faculty of Communication and Informatics (FKI) at Muhammadiyah University of Surakarta. The research method employed in this study is a quantitative approach. The study population consists of 2024 FKI students at Muhammadiyah University of Surakarta who actively use the TikTok app. The research sample consisted of 150 FKI UMS students from the class of 2024 who follow the Whitelab TikTok account. Data collection was conducted via an online questionnaire consisting of two sections: one to measure the level of exposure to Whitelab’s TikTok content and the other to measure interest in purchasing skincare products. The research instrument utilized a Likert scale. Data analysis was performed using SPSS software with simple linear regression and t-tests. The results of this study indicate that Whitelab’s TikTok content has a positive and significant impact on the purchase intent of skincare products among 2024 FKI UMS students. Engaging, informative, and relevant content has been proven to shape positive perceptions, build trust, and drive the desire to purchase, particularly among students as active social media users. This demonstrates that social media, particularly TikTok, plays a crucial role as a digital marketing tool in influencing the behavior of the younger generation. Thus, effective TikTok content can serve as a marketing communication strategy capable of increasing consumer purchase intent, especially among students as active social media users. Keywords: Content; purchasing interest; TikTok; whitelab.   Abstrak Perkembangan pesat media sosial, khususnya platform berbasis video seperti TikTok, telah mengubah cara konsumen, terutama generasi muda, dalam memperoleh informasi dan mengambil keputusan pembelian. Platform ini dimanfaatkan oleh berbagai merek, termasuk Whitelab, untuk menyampaikan konten promosi yang menarik dan informatif guna membangun persepsi serta meningkatkan minat beli konsumen. Tujuan penelitian ini ialah menganalisis pengaruh konten TikTok Whitelab terhadap minat beli produk skincare di kalangan mahasiswa Fakultas Komunikasi dan Informatika (FKI) Universitas Muhammadiyah Surakarta. Metode penelitian yang digunakan dalam penelitian ini ialah metode kuantitatif. Populasi penelitian mencakup mahasiswa FKI Universitas Muhammadiyah Surakarta angkatan 2024 yang aktif menggunakan aplikasi TikTok. Sampel penelitian berjumlah 150 mahasiswa FKI UMS angkatan 2024 yang mengikuti akun TikTok Whitelab. Pengumpulan data dilakukan melalui kuesioner online yang terdiri atas dua bagian, yaitu untuk mengukur tingkat paparan terhadap konten TikTok Whitelab dan minat beli produk skincare. Instrumen penelitian menggunakan skala Likert. Analisis data dilakukan menggunakan program SPSS dengan metode regresi linier sederhana dan uji t. Hasil penelitian ini ialah konten TikTok Whitelab memiliki dampak positif dan signifikan pada minat beli produk skincare pada mahasiswa FKI UMS Angkatan 2024. Konten yang menarik, informatif, dan relevan terbukti mampu membentuk persepsi positif, menumbuhkan kepercayaan, serta mendorong keinginan untuk membeli, terutama pada mahasiswa sebagai pengguna aktif media sosial. Hal ini menunjukkan bahwa media sosial, khususnya TikTok, memiliki peran penting sebagai sarana pemasaran digital dalam memengaruhi perilaku konsumen generasi muda. Dengan demikian, konten TikTok yang efektif dapat menjadi strategi komunikasi pemasaran yang mampu meningkatkan minat beli konsumen, terutama di kalangan mahasiswa sebagai pengguna aktif media sosial. Kata-kata kunci: Konten; minat beli; Tiktok; whitelab.